Implications of Quasi-Fiscal Activities in Ghana - Chivakul, Mali.; York, Robert (Washington, D.C. : International Monetary Fund, 2006)
This paper assesses the scope and coverage of quasi-fiscal activities (QFAs) in Ghana. We find that while QFAs have been reduced recently, they remain significant. The extensive nature of these activities has several macroeconomic and structural policy implications. An extended measure of public sector operations, including QFAs, presents a clearer picture of Ghana's fiscal stance and fiscal adjustment from one for the central government alone; QFAs have led to serious distortions in energy and water consumption; and they have distorted the investment decisions of both public enterprises and the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet